2014
DOI: 10.1002/smll.201401965
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Oxidation of Monodisperse Silicon Nanocrystals with Allylphenylsulfide Surfaces

Abstract: The synthesis and characterization of size-separated silicon nanocrystals functionalized with a heteroatom-substituted organic capping group, allylphenylsulfide, via photochemical hydrosilylation are described for the first time. These silicon nanocrystals form colloidally stable and highly photoluminescent dispersions in non-polar organic solvents with an absolute quantum yield as high as 52% which is 20% above that of the allylbenzene analogue. Solutions of the size-separated fractions are characterized over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 39 publications
1
37
0
3
Order By: Relevance
“…Silyl radicals react with the terminal carboncarbon bond to induce as table SiÀCb ond. [88,125] One of those reports shows the effect on photoluminescence of an aged silanized Si surface.Z ou and Kauzlarich [88] prepared silanized Si particles through amulti-step functionalization:s tarting with chloride terminated Si, hydroxy terminated particles were obtained after the addition of methanol and then water. [120] 2) Functionalization of halide-terminated silicon (Si À Cl) is mostly achieved via the Grignard reaction through the addition of RMgBr or RLi (when Ri sa na lkyl group).…”
Section: Silicon Oxidation and Post-synthesis Surface Modificationmentioning
confidence: 99%
“…Silyl radicals react with the terminal carboncarbon bond to induce as table SiÀCb ond. [88,125] One of those reports shows the effect on photoluminescence of an aged silanized Si surface.Z ou and Kauzlarich [88] prepared silanized Si particles through amulti-step functionalization:s tarting with chloride terminated Si, hydroxy terminated particles were obtained after the addition of methanol and then water. [120] 2) Functionalization of halide-terminated silicon (Si À Cl) is mostly achieved via the Grignard reaction through the addition of RMgBr or RLi (when Ri sa na lkyl group).…”
Section: Silicon Oxidation and Post-synthesis Surface Modificationmentioning
confidence: 99%
“…[31] For size-sorted samples exposed to air for the same amount of time, it was found that the PL QY of larger ncSi fractions was most sensitive to oxidation, (Figure 4a). [32] By monitoring the time dependent changesi nt he PL wavelength and QY of ncSi exposed to dry and humid argon and oxygen, the oxidation was provent ob ew ater-assisted (Figure 4b). [33] The more pronounced PL blueshift of the larger ncSi was associated with the more pronounced shrinkage of the ncSi core due to oxidation, even thought he smaller surface curvature is expected to impede the initial stages of reaction with oxygen and water.…”
Section: Oxidationmentioning
confidence: 97%
“…In practice, the PL would blueshift and the QY would decrease with time of exposure to air, and the oxidation is often assisted by water . For size‐sorted samples exposed to air for the same amount of time, it was found that the PL QY of larger ncSi fractions was most sensitive to oxidation, (Figure a) . By monitoring the time dependent changes in the PL wavelength and QY of ncSi exposed to dry and humid argon and oxygen, the oxidation was proven to be water‐assisted (Figure b) .…”
Section: Size Effect On Stability and Cytotoxicitymentioning
confidence: 99%
“…Dieser Effekt ergibt sich vermutlich aus der damit verbundenen Senkung der C-X-Schwingungsfrequenz. [41] Bis auf wenige Ausnahmen [42] bençtigt die thermische Hydrosilylierung hohe Reaktionstemperaturen, weshalb fast ausschließlich hochsiedende Alkene und Alkine auf SiNKOberflächen gebunden werden kçnnen. Daneben existiert die photochemische Hydrosilylierung als Alternative,d eren Einsatzfähigkeit allerdings durch grçßenabhängige Reaktivität der SiNKs,I ntoleranz gegenüber funktionellen Gruppen, wie auch die bençtigten langen Reaktionszeiten limitiert ist.…”
Section: Hydrosilylierungunclassified